Perbedaan Kadar Hemoglobin dan Morfologi Eritrosit Sebelum Menstruasi dan Setelah Menstruasi Remaja Putri - Risma Ayu Asfaraini; Siti Zaetun; Rohmi Rohmi (Politeknik Kesehatan Kemenkes RI Jakarta I, 2017)
ABSTRACT Adolescence is characterized by the functioning of reproductive organs such as menstruation. Throughout the reproductive age, women will experience blood loss due to menstrual events. Thus the loss of iron will cause a decrease in hemoglobin levels in the blood and will cause anemia. This research to determine differences in hemoglobin levels and morphological features of erythrocytes before and after menstruation in young women in Nurul Hakim Kediri Islamic Boarding School. This study used an observational analytic study design. The population was 185 people and a sample of 30 people. The sampling technique uses non random accidental sampling. Analysis of the data used is bivariate data analysis using independent T-Test statistical test analysis. Erythrocyte morphology is analyzed in a descriptive manner. The results showed that the average hemoglobin level of students before menstruation was 13.2 g% and after menstruation 11.8 g%. Morphology of erythrocytes before menstruation and after menstruation on average found abnormal erythrocyte Shape (shape) while in terms of Size (size), 25% have small size (microcytic) and in terms of staining (staining), 47% of the coloring is abnormal. Conclusion after the T-test, there was a difference in the mean Hemoglobin level before and the mean Hemoglobin level after Menstruation in young women namely the hemoglobin level was lower than before menstruation. Keywords : Hemoglobin Levels, Erythrocyte Morphology, Young Women, Menstruation